2017
DOI: 10.1186/s40623-017-0695-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of a locked fault: investigation of the Ganos segment of the North Anatolian Fault using three-dimensional magnetotellurics

Abstract: This study attempts to reveal the fault zone characteristics of the locked Ganos Fault based on electrical resistivity studies including audio-frequency (AMT: 10,400-1 Hz) and wide-band (MT: 360-0.000538 Hz) magnetotellurics near the epicenter of the last major event, that is, the 1912 Mürefte Earthquake (M w 7.4). The AMT data were collected at twelve stations, closely spaced from north to south, to resolve the shallow resistivity structure to 1 km depth. Subsequently, 13 wide-band MT stations were arranged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 71 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…Analogously, lack of fluids in the vicinity of faults can infer to near hydrostatic pore pressures that may lead to longer times of stress accumulation and larger rupture events. Previously, MT measurements made on locked strikeslip faults demonstrated a characteristic portrayed by the presence of resistive bodies at both sides of the fault (e.g., Unsworth et al 1999;Goto et al 2005;Tank et al 2003;Tank 2012;Karaş et al 2017). Both the metamorphic units of CPS (R 2 ) and mafic units south of the NAF (R 1 ) can be interpreted as reasonable geological bodies to resist such inclusion of fluids due to their low porosity values or poor interconnection between their pores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analogously, lack of fluids in the vicinity of faults can infer to near hydrostatic pore pressures that may lead to longer times of stress accumulation and larger rupture events. Previously, MT measurements made on locked strikeslip faults demonstrated a characteristic portrayed by the presence of resistive bodies at both sides of the fault (e.g., Unsworth et al 1999;Goto et al 2005;Tank et al 2003;Tank 2012;Karaş et al 2017). Both the metamorphic units of CPS (R 2 ) and mafic units south of the NAF (R 1 ) can be interpreted as reasonable geological bodies to resist such inclusion of fluids due to their low porosity values or poor interconnection between their pores.…”
Section: Resultsmentioning
confidence: 99%
“…Many segments can be interpreted as seismic gaps (Ergintav et al 2014), while the surface creep (Çakır et al 2005) or microseismic activity (Örgülü 2011) is also valid explanations for release of stress. Karaş et al (2017) showed that even in small distances within the same segment of the NAF, structures of faults might show drastically different characteristics, thus leading to heterogeneous rheological environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent works focus on geophysical survey for deep geological and tectonic quaternary basin characterization (Boncio et al 2016;T€ un et al 2016;Civico et al 2017;Mekkawi et al 2017;Nocentini et al 2017;Onnis et al 2017). Furthermore, most recently reflection seismic and magnetotelluric surveys provide high-resolution images of fault systems (Improta et al 2017(Improta et al 2010Balasco et al 2015;Beckers et al 2015;Beilecke et al 2016;Beka et al 2017;Karaş et al 2017;Buttinelli et al 2016) giving a relevant support to seismologists and structural geologists.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate a separation between TE and TM mode in both apparent resistivity and phase at low frequencies in proximity to the coast line (Pous et al, 2002;Lezaeta & Haak, 2003). Large scale faults also impact magnetotelluric data and inversion, and similarly many MT studies have investigated the influence of these structures (Unsworth & Bedrosian, 2004;Bedrosian et al, 2002;Wannamaker et al, 2004;Karaş et al, 2017). In most of these studies, MT data was collected across the fault zone.…”
Section: Introductionmentioning
confidence: 99%